Copyright Protection of Owners for Commercialized Use of Created Song Without Permission - Maria Priska Seran; Lukman Hakim; Muhammad Ramadhana Alfaris (Dialogia Iuridica)
The current increase in the music industry in Indonesia is in line with the development of the complexity of the legal issues that accompany it. This then triggers the emergence of disputes over works in the music industry in cases of copyright for a work. Like the copyright infringement case that occurred between Ahmad Dhani and Once Mekel. This research aims to answer two legal issues, namely to analyze legal protection for copyright holders for commercial use of written songs without permission and to determine the legal consequences for commercial use of written songs without the creator's permission. The research method used in this research is analytical descriptive which describes the problems that occur which will be explained qualitatively. Based on the existing analysis, Ahmad Dhani has carried out preventive protection by informing the media that there is a prohibition on performing the song Dewa19 at commercial music concerts. The legal consequences for both civil and criminal violations have been regulated in Article 113 of Law No. 28 of 2014 concerning Copyright for violation of Economic Rights. The conclusion of this research is the issuance of Government Regulation No. 56 of 2021 to prioritize legal certainty and legal protection for creators regarding economic rights. The song copyright violation was committed by Once Mekel who sang the song Dewa19 without Ahmad Dhani's permission and did not pay royalties and this violation is regulated in Article 113 of Law No. 28 of 2014 concerning Copyright.